IMF conditionality: experience under stand-by and extended arrangements : Part 11: Background papers - Schadler, Susan (Washington, D.C. International Monetary Fund, 1995)
This book present detailed examinations of selected policy issues in five background papers.
IMF occasional paper 129
Includes bibliographical references
osa 5/9/16
Loans
Keywords: International Monetary Fund; International finance; Structural adjustment (economic policy) - developing countries